Accountability in the global health regime : a critical examination of the institutional policy and practice of the global fund to fight HIV/AIDS, tuberculosis and malaria partnership programme in Ghana - Onokwai, John Chukwuemeka (Rhodes University, Faculty of Humanities, Department of Political and International Studies)
The overarching objective of this thesis is to undertake a critical examination of the institutional accountability policy and practice of the Global Fund to Fight AIDS, Tuberculosis and Malaria (Global Fund) in the context of its partnership programme in Ghana. The Global Fund is a global public-private partnership (GPPP) in health engaged in public health policy processes worldwide. As a GPPP, the policy mandate that underpins its global response to fight the aforementioned diseases requires it to enter into partnerships with recipient countries to finance their national health policy responses and strategies to tackle these diseases. Situating accountability within the context of the shift from an international health to a global health regime, the study argues that the emergence of GPPPs in health and the formal policy mandate and decision-making powers they exercise have had knock-on consequences for understanding accountability in the global health regime. This is because while the understanding of accountability for public health policy processes in the international health regime revolved solely around state-based and state-led accountability processes, it is no longer so in current global health regime. Since these GPPPs are not states, they derive their understanding of accountability from the nature and character of their individual policy and practice arrangements. However, despite contestation around the Global Fund's accountability in global health literature, this literature has little to say on the question of how the Global Fund itself (as a partnership organisation) understands accountability in policy and how this understanding informs its practice in specific settings of global health. Thus, this study contributes to literature on GPPPs' accountability in global health by specifically exploring how the Global Fund understands accountability in policy and how this understanding informs its accountability in practice, in particular in relationship to its implications for country ownership of health policy in Ghana. Drawing on fieldwork undertaken in Ghana, and guided by a critical political economy approach, this study will demonstrate how: 1) the Global Fund's institutional policy and practice arrangements undermine accountability to the government and to those affected by their activities; 2) the Global Fund's practice of country ownership is reflective of conditional ownership despite the fact that the Global Fund claims to promote country ownership as a core principle of its accountability practice in aid recipient countries; and 3) the accountability policy and practice instruments of the Global Fund are not politically neutral, but are rather a function of relations of power. To improve the ability of Ghana (and other recipient countries) to own their developmental policies, a reordering of global economic relations is needed, with a renewed emphasis and focus on economic justice and human rights. Such a reordering will improve the material capabilities (control of and access to global centres of production, finance and technology) of aid recipient countries. This will empower Ghana (and other recipient countries) to play a more dominant, rather than a subsidiary role in how the global health landscape is organised and financed and in policy processes undertaken by global health policy institutions like the Global Fund. In this way, Ghana (and other developing countries) will be able to limit and mitigate the dominance and influence of powerful donors who shape the institutional policy and practice arrangements of global health policy institutions like the Global Fund.
Keywords: World health; Global Fund to Fight AIDS, Tuberculosis, and Malaria -- Administration; Public-private sector cooperation -- Political aspects; Public-private sector cooperation -- Social aspects; Public-private sector cooperation -- Administration; Medical policy -- Ghana; Public health laws, International; Ghana -- Social conditions